2010
DOI: 10.1007/s00436-010-2216-0
|View full text |Cite
|
Sign up to set email alerts
|

Differences in efficacy of monepantel, derquantel and abamectin against multi-resistant nematodes of sheep

Abstract: Drug resistance has become a global phenomenon in gastrointestinal nematodes of sheep, particularly resistance to macrocyclic lactones. New anthelmintics are urgently needed for both the control of infections with multi-resistant nematodes in areas where classical anthelmintics are no longer effective, and the prevention of the spread of resistance in areas where the problem is not as severe. Recently, two new active ingredients became commercially available for the treatment of nematode infections in sheep, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 23 publications
0
36
0
4
Order By: Relevance
“…Bustamante et al (2009) found that monepantel was 100% effective in sheep in Brazil, Argentina and Uruguay. However, resistance to monepantel (SCOTT et al, 2013;MEDEROS et al, 2014a; VAN DEN BROM et al, 2015) and to derquantel (KAMINSKY et al, 2011) has been reported around the world, demonstrating the high vulnerability of these drugs. It is likely that reports of resistance to these anthelmintics will soon be published in Brazil.…”
Section: History Of Ahr In Small Ruminants In Brazil and Around The Wmentioning
confidence: 99%
See 1 more Smart Citation
“…Bustamante et al (2009) found that monepantel was 100% effective in sheep in Brazil, Argentina and Uruguay. However, resistance to monepantel (SCOTT et al, 2013;MEDEROS et al, 2014a; VAN DEN BROM et al, 2015) and to derquantel (KAMINSKY et al, 2011) has been reported around the world, demonstrating the high vulnerability of these drugs. It is likely that reports of resistance to these anthelmintics will soon be published in Brazil.…”
Section: History Of Ahr In Small Ruminants In Brazil and Around The Wmentioning
confidence: 99%
“…Recently, two new classes of anthelmintics were launched, an amino-acetonitrile derivative, monepantel (KAMINSKY et al, 2008), and derquantel, which was marketed in association with abamectin (LITTLE et al, 2010). However, there have been reports of resistance to monepantel (SCOTT et al, 2013;MEDEROS et al, 2014a; VAN DEN BROM et al, 2015) and to derquantel (KAMINSKY et al, 2011), indicating the high vulnerability of these drugs. Additional to the loss of effectiveness there are the effects of toxic residues on nontarget organisms in the environment (LUMARET et al, 2012) and of residues in meat (COOPER et al, 2011), milk and other animal products associated to anthelmintics (IMPERIALE et al, 2004;ANASTASIO et al, 2005;WHELAN et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Monepantel, a derivative of aminoacetonitrile, is the most recent alternative in the chemical control of gastrointestinal parasites in sheep (HOSKING et al, 2010;KAMINSKY et al, 2011;SAGER et al, 2012). However, after three years of commercialization, it has already demonstrated resistant cases in New Zealand (SCOTT et al, 2013), Uruguay (MEDEROS et al, 2014) and the Netherlands ( VAN DEN BROM et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Derquantel is semisynthetic derivative of paraherquamide A isolated from natural spiroindoles -products of Penicillium paraherquei (86,87). Derquantel inhibits nAChR (88), it has a broad spectrum of anthelmintic actions; the mixture derquantel-abamectin is often used in treatment and control of various nematodes in the gastrointestinal tract (even ones resistant to other drugs), which allows to expect finding anthelmintic properties in similar compounds. Tribendimidin is an aminophenyldimidin derivative of amidantel; it was first synthesized in China in 1980 (89) and introduced in local medical practice in 2004 (90-92).…”
Section: +mentioning
confidence: 99%